2020
DOI: 10.3390/biomedicines8080286
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoids in p53—Mediated Immune Dysfunctions Linking to Cancer Prevention

Abstract: The p53 protein plays a central role in mediating immune functioning and determines the fate of the cells. Its role as a tumor suppressor, and in transcriptional regulation and cytokine activity under stress conditions, is well defined. The wild type (WT) p53 functions as a guardian for the genome, while the mutant p53 has oncogenic roles. One of the ways that p53 combats carcinogenesis is by reducing inflammation. WT p53 functions as an anti-inflammatory molecule via cross-talk activity with multiple immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 220 publications
(224 reference statements)
0
17
0
Order By: Relevance
“…Phosphorylation. Phosphorylation responses to DNA damage and other stresses are controlled by regulators, subcellular localization, stability, and transcriptional activation of target genes, which prompts the biological effects [116,117]. Several kinases target specific serine and threonine residues within p53 for phosphorylation [118].…”
Section: Regulatory Mechanism Of the P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation. Phosphorylation responses to DNA damage and other stresses are controlled by regulators, subcellular localization, stability, and transcriptional activation of target genes, which prompts the biological effects [116,117]. Several kinases target specific serine and threonine residues within p53 for phosphorylation [118].…”
Section: Regulatory Mechanism Of the P53mentioning
confidence: 99%
“…Flavonoids. Flavonoids are suggested to reduce p53mediated chronic inflammation leading to cancer progression [161]. Quercetin can induce phosphorylation of ATM and phosphorylation of histone H2AX; therefore, p53 accumulation and phosphorylation occurred in ATM-deficient cells, indicating that ATM is not required for quercetininduced p53 phosphorylation [162].…”
Section: P53 Signaling Pathway Modulated By Dietary Antioxidantsmentioning
confidence: 99%
“…The studies carried out with propolis from Asia showed that apoptosis by the mitochondrial pathway and the regulation of p53 could be the mechanism through which cell death is promoted by the extracts. Reports stated that some of the compounds commonly found in propolis are capable of regulating p53 [ 174 ]. This is promising for investigating the mechanisms of action of propolis in different types of cancer, so we think that it is necessary to replicate these studies using different cell lines and studies with 3D cultures.…”
Section: Biomedical Properties Of Propolis On Diabetes Obesity Amentioning
confidence: 99%
“…p53 is another key mediator that switches its functions between DNA repair and/or cell death upon cellular stress/stimulus (Siddiqui et al, 2020). We observed an upregulated p‐p53 level in MCF‐7 cells, while a mutant p53 remained unchanged in MDA‐MB‐231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…ATM‐Chk2 and ATR‐Chk1 pathways are well established upon stress conditions, a process regulated by the p53 tumor suppressor gene (Ou, Chung, Sun, & Shieh, 2005; Ramadan et al, 2020). p53 regulates apoptosis by activating DNA damage response (DDR) mechanisms in response to an external stimuli/stress and/or initiates the DNA repair process if the damage level is repairable (Siddiqui, Rahman, Rupasinghe, & Vazhappilly, 2020). Studies have shown that the p53 activation also initiates a downstream cascade, p21‐mediated cell cycle arrest in breast cancer cells (Shamloo & Usluer, 2019).…”
Section: Introductionmentioning
confidence: 99%